A draft genome sequence for the Ixodes scapularis cell line, ISE6 - Miller, Jason R. (F1000Res, 2018)
Background: The tick cell line ISE6, derived from Ixodes scapularis, is commonly used for amplification and detection of arboviruses in environmental or clinical samples. Methods: To assist with sequence-based assays, we sequenced the ISE6 genome with single-molecule, long-read technology. Results: The draft assembly appears near complete based on gene content analysis, though it appears to lack some instances of repeats in this highly repetitive genome. The assembly appears to have separated the haplotypes at many loci. DNA short read pairs, used for validation only, mapped to the cell line assembly at a higher rate than they mapped to the Ixodes scapularis reference genome sequence. Conclusions: The assembly could be useful for filtering host genome sequence from sequence data obtained from cells infected with pathogens.